The use of small airplanes to gather swan data in Alaska - King, James G (Wildfowl, 1973)
Single engine airplanes have been used in Alaska for swan population counts over the past 17 years. Five different methods have been developed: (1) complete census; (2) random plot census; (3) line transect surveys; (4) random flight method; (5) exploratory flight method. The first two methods are recommended when full time can be devoted to swan work. The last three are used when the flight is primarily for other purposes.